Ghost fleet awakened : Lake George's sunken bateaux of 1758 - Zarzynski, Joseph W. (Excelsior editions, 2019)
""Ghost Fleet" Awakened is the untold story of a little recognized sunken fleet of British warships from the French and Indian War (1755-1763). In the autumn of 1758, the British command at Lake George, New York made a daring decision. Without a fortification to protect their battle crafts, since the French and their Native American allies destroyed Fort William Henry in August 1757, the British deliberately sank two floating batteries (radeaux), some row galleys and whaleboats, a sloop, and 260 bateaux. This placed the warships into wet storage, protecting them from marauding French over the winter of 1758-1759. Many submerged boats were raised in 1759, but some were not. In 1960, two divers rediscovered several sunken bateaux. The media dubbed the sunken boats the "Ghost Fleet." These shipwrecks were the focus of underwater archaeological investigations that provided archaeologists with opportunities to gain unprecedented insight into eighteenth century lifeways. This book takes readers on a journey that began over 250 years ago, when bateaux first plied the waters of this mountain lake. It enlightens readers with a history of these utilitarian vessels, including their origins and uses. The author infuses the book with underwater archaeology doctrine, so readers understand the nautical significance of these colonial craft. Furthermore, the book examines shipwreck preservation techniques, the creation of shipwreck parks for scuba enthusiasts, and the many multi-faceted programs developed by the non-profit organization Bateaux Below to help protect these finite cultural resources."--Provided by publisher